The Meaning of Ujungan Tradition in Seren Taun Ceremony: A Phenomenological Study of Kasepuhan Cibadak Community - Sugiarta, Nugraha; Anggraeni, Risa; Reza, Faisal (Sinergi International Journal of Communication Sciences, 2024)
The Ujungan tradition is an attraction performed by a group of people, where participants whip each other using rattan. This tradition is held once a year during the Seren Taun traditional ceremony. The purpose of this study is to explore the experiences, motives, and meanings of the Ujungan tradition for its performers within the Kasepuhan Cibadak community, Lebak Regency, Banten. This study employs a qualitative method with Alfred Schutz’s phenomenological approach. Primary data collection techniques include active participant observation and semi-structured interviews, while secondary data are obtained from document studies/documentation. The study involves four key informants who are Ujungan performers and two supporting informants, consisting of spectators and cultural experts. Data validity is ensured through source triangulation. The findings reveal that the performers experience emotional enjoyment. The "because motives" are influenced by the role of traditional leaders and the performers’ self-awareness as part of the Kasepuhan Cibadak community. Meanwhile, the "in-order-to motives" focus on preserving the Ujungan tradition as a cultural heritage. For the performers, the Ujungan tradition carries meanings of tradition, ritual, and karesmen (artistic expression). Therefore, the Ujungan tradition in the Kasepuhan Cibadak community, Lebak Regency, Banten, is regarded as entertainment with local wisdom values. The tradition also fosters values of togetherness and trust, symbolizing protection for circumcised boys, ensuring their safety from misfortune.